Extrato aquoso das folhas e óleo da semente de moringa em substituição ao antimicrobiano na dieta de frangos de corte - Lima, Karolayne Rayara Santos de (2023)
The objective of this study was to evaluate the effects of aqueous leaf extract of moringa leaves (ALEM) and moringa seed oil (MSO) replacing zinc bacitracin in the diet of broilers on feed digestibility, development of villi and intestinal crypts, performance, carcass yield, cuts and organs. 336 broilers from 1 to 42 days of age were used, divided into seven treatments and six replications. The treatments were: positive control diet containing zinc bacitracin; negative control diet without additives; diet containing 0.20% MSO and four diets containing ALEM levels (0.25, 0.50, 0.75 and 1.0%). The variables evaluated were: DM and CP digestibility of the diets; villus height, crypt depth and villus/crypt ratio (V/C) in the duodenum and jejunum; feed consumption, weight gain and feed conversion (FC); hot carcass yields (HCY), cold carcass yields (CCY) and commercial cuts; and relative weight of the organs. The results were subjected to analysis of variance and F test for orthogonal contrasts, at 5% probability. ALEM levels were subjected to regression analysis. ALEM and MSO resulted in greater digestibility for DM and CP, greater villus heights, V/C ratio and lower crypt depth than the control treatments. There was no effect of the treatments on the FC of the broilers. The addition of moringa resulted in greater weight of the proventricle, thigh, drumstick and back. There was a linear increase in the height of the duodenum villi and the V/C ratio of the jejunum, a linear reduction in the depth of the jejunum crypt, maximum crypt depth and the V/C ratio in the jejunum at the level of 0.56% addition of ALEM. It is concluded that ALEM and MSO can be used as a substitute for zinc bacitracin for broilers.